2020
DOI: 10.3389/fpsyg.2019.03048
|View full text |Cite
|
Sign up to set email alerts
|

Examining Ownership Equity as a Psychological Factor on Tourism Business Failure Forecasting

Abstract: This paper examines ownership equity as a predictor of future business failure within the tourism and hospitality sectors. The main goals of this study were to examine which ratios are the most important for a tourism business failure forecasting model and how significant is the "total percentage of equity ownership by company directors" ratio compared with other ratios associated with the probability of bankruptcy. A stepwise weight assessment ratio analysis (SWARA) was applied, and 12 tourism bankruptcy expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
(46 reference statements)
0
9
0
1
Order By: Relevance
“…It is argued that, because management in the tourism industry field sometimes requires immediate decisions (Murphy, 1985), it is difficult to ensure that all voices are represented in the decision-making process (Nault and Stapleton, 2011). However, using forecasting models can address and ease strategic and urgent decision-making because it can assess weakness in order to minimize any risks (Korol and Spyridou, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is argued that, because management in the tourism industry field sometimes requires immediate decisions (Murphy, 1985), it is difficult to ensure that all voices are represented in the decision-making process (Nault and Stapleton, 2011). However, using forecasting models can address and ease strategic and urgent decision-making because it can assess weakness in order to minimize any risks (Korol and Spyridou, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Scheyvens ( Scheyvens, 2002 ), identified that inadequate resources, information, and consultation to make an effective engagement with stakeholders can lead to vulnerability in tourism. Financial risks are always an initially significant factor for business success or failure in communities ( Korol and Spyridou, 2020 ). When finance is unavailable at a local level, communities will lose their own control of resources to outside enterprises ( Scheyvens, 2002 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Borodin, Pyatanova ve Yashin (2019), iflas etmiş 5 havayolu işletmesinin finansal verileri üzerinde Bayes regresyon analizini uygulayarak net gelir, likidite oranı, doluluk oranı ve aktif devir hızı gibi oranların finansal başarısızlık riskini %90'a kadar doğru tahminde bulunduğu sonucuna ulaşmışlardır. Korol ve Spyridou (2020), turizm sektöründeki finansal başarısızlığı tahmin edebilmek için hangi oranların önemli olduğunu Swara analizi ile incelemişler ve işletme sermayesi/toplam varlıklar, dağıtılmamış kârlar/toplam varlıklar ve faiz ve vergi öncesi kar/toplam varlıklar oranlarının en önemli oranlar olduğunu belirlemişlerdir.…”
Section: Literatürunclassified
“…As it is natural, when there is an intense crisis in an area, corporate companies tend to go bankrupt more easily as the instability problems increase, and liquidity difficulties usually arise [2]. Although there is a plethora of studies that are trying to explain business failure for different countries under normal circumstances, there are limited studies that focus on the company's business failure for a country under crisis [3]. Business failure can be described in different ways, since it mainly depends on the specific condition the company deals with, during a specific period.…”
Section: Introductionmentioning
confidence: 99%